If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(3s + 6) = -6(4s + -6) Reorder the terms: 12(6 + 3s) = -6(4s + -6) (6 * 12 + 3s * 12) = -6(4s + -6) (72 + 36s) = -6(4s + -6) Reorder the terms: 72 + 36s = -6(-6 + 4s) 72 + 36s = (-6 * -6 + 4s * -6) 72 + 36s = (36 + -24s) Solving 72 + 36s = 36 + -24s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '24s' to each side of the equation. 72 + 36s + 24s = 36 + -24s + 24s Combine like terms: 36s + 24s = 60s 72 + 60s = 36 + -24s + 24s Combine like terms: -24s + 24s = 0 72 + 60s = 36 + 0 72 + 60s = 36 Add '-72' to each side of the equation. 72 + -72 + 60s = 36 + -72 Combine like terms: 72 + -72 = 0 0 + 60s = 36 + -72 60s = 36 + -72 Combine like terms: 36 + -72 = -36 60s = -36 Divide each side by '60'. s = -0.6 Simplifying s = -0.6
| 2y=16+5x | | -4(2-x)=-4x+10 | | Z+3= | | 0.7(3x+3)=1.1-(x+6) | | 10x-x^2=3x+10 | | 3x*3y=126 | | 3+2.25n=4+2n | | -30w+2=-24w-7 | | 4t-2-2+7= | | (5x-54)+(3x+16)=360 | | 4(2-x)=-4x+20 | | 1250=5n-5000 | | -3x=-2.1 | | 12=3y-7+4y | | 16(v+2)-4v=3(4v+1)-10 | | 9(x+3)-6=26-2x-5+11x | | 20x=8x+80 | | 0.4x-0.8(6-x)=-0.6 | | 34+2x-x= | | 25500+2000(n)=47900-800(n) | | 10=-5y-5x | | 4x^2+29x-332=0 | | 30x=7x+90 | | 87+4-2y=22 | | h=5vt+13t^2forv | | 210x+25=210x-15 | | 5w-15=-2w-30 | | 20+3c=69 | | (X^3)+4x-1=4 | | 0=2x^2-9x+7 | | 16x+2=15x-3+5 | | x^2+y-4x+6y-12=0 |